BIOFLOK: Budidaya Ikan Lele Sebagai Upaya Pemanfaatan Lahan Desa Guntung Dan Pemulihan Perekonomian Di Era Newnormal - Rusandi, M. Arli (Journal of Community Engagement Research for Sustainability, 2024)
The decline in turnover and the loss of jobs for some people after the COVID 19 pandemic phenomenon. Therefore, we hold service activities that can be a solution to restore the community's economy in the new normal life by cultivating catfish with biofloc techniques based on the use of vacant land. Catfish is one of the most popular types of fish because in addition to being relatively affordable for the general public, it is also easy to obtain. The purpose of this service program is to increase community turnover through catfish farming using biofloc techniques. To overcome this problem, the activities carried out include (1) Counseling and mentoring on biofloc techniques, (2) Counseling on how to care for catfish with biofloc techniques, (3) Counseling on how to care for and maintain biofloc technique ponds. The results of this service activity are shown by the increased motivation of partners to carry out catfish farming as an effort to improve the welfare of the PKK women group in Guntung Village. The counseling that has been carried out has succeeded in increasing the knowledge of the PKK groups to increase crop yields with biofloc techniques, both for disease control and maintenance and feeding methods.